Changes in autistic trait indicators in parents and their children with ASD: A preliminary longitudinal study. Issue 3 (30th August 2015) - Hasegawa, Chiaki; Kikuchi, Mitsuru; Yoshimura, Yuko; Hiraishi, Hirotoshi; Munesue, Toshio; Takesaki, Natsumi; Higashida, Haruhiro; Oi, Manabu; Minabe, Yoshio; Asada, Minoru
Abstract: This study investigated whether the longitudinal changes in symptom severity in children with autism spectrum disorder (ASD) are associated with changes in the parents׳ autistic traits. The results demonstrated two significant correlations between the changes in children׳s Social Responsiveness Scale (SRS) scores and the Social Responsiveness Scale (SRS) score changes in either the father or both parents. Autistic symptom mitigation in ASD children was associated with increased empathy levels in their parents. Highlights: ● We investigated the autistic trait in ASD children and parents. ● Changes in autistic trait in children were correlated with those in parents. ● Mitigation in ASD children was associated with decrease of empathy levels in parents.